4475 Shares

How to solve the equation | m - 9 | = 27 ?

How to solve the equation | m - 9 | = 27 ? Topic: How to solve the equation | m - 9 | = 27 ?
July 18, 2019 / By Joss
Question: I can't really find how to solve this on the internet and I have a lot of questions like it. I don't just want the answer. I have the answers. I just really would like to know how to solve the problems and other one's like this so I can show my work. Thank you. (: Thank you everyone, Also, I need help solving these problems: "Solve the given inequality. Describe the solution set using the set-builder or iinterval notation. Then, graph the solution set on a number line." m+4 greater than or equal to 2.
Best Answer

Best Answers: How to solve the equation | m - 9 | = 27 ?

Gerry Gerry | 5 days ago
Maynor's correct m - 9 = 27 m = 36 m - 9 = -27 m = -18 If you substitute 27 and -18 into the original equation, you'll find that they both work. |36 - 9| = 27 |27| = 27 27 = 27 |-18 - 9| = 27 |-27| = 27 27 = 27 ANSWER m = 36, -18
👍 118 | 👎 5
Did you like the answer? How to solve the equation | m - 9 | = 27 ? Share with your friends
Gerry Originally Answered: Graphing equation question? how would solve this linear equation?
2x + 3(11/3) = 12 3/1 * 11/3 = 33/3 When multiplying, just multiply across, numerator to numerator and denominator to denominator. (I know I put a 1 under the 3, all whole numbers have a 1 under them) (example : 3/1 = 3) or ( lets say 5 in fraction form is 5/1 ) (Another fraction example 2/5 * 3/4 mult across and you get 2 * 3 = 6 and 5 * 4 = 20 answer 6/20 then, simplify and get 3/10) Now simplify 33/3 = 11 2x + 11 = 12 Now subtract 11 from both sides. and you get 2x = 1 2x = 1 Now divide 2 on both sides and you get x = 1/2 ordered pair is (1/2 , 11/3)
Gerry Originally Answered: Graphing equation question? how would solve this linear equation?
2x + 3(11/3) = 12 look at 3(11/3) = (3 * 11) / 3 = 11 ( 3/3) = 11 that gives you 2x + 11 = 12 2x = 1 x = 1/2 the point (1/2 , 11/3) is a solution to the equation remember, when you multiply fractions, you multiply the tops and multiply the bottoms if there isn't a bottom for one of the fractions, treat it like 1 3(11/3) = (3/1)(11/3) = (3*11) / (1 * 3) = 33 / 3 = 11

Delphine Delphine
Well the absolute value bars make it so the problem is now read as two seperate problems. m-9=27 +9 +9 m=36 and m+9=27 -9 -9 m=-18
👍 40 | 👎 3

Cailyn Cailyn
it's called absolute value so the answer is solved with this: m - 9 = 27 m - 9 = -27 So the answer is: m = 36 ; m = -18
👍 36 | 👎 1

Cailyn Originally Answered: Solve this equation; like a quadratic equation.?
With substitution it becomes a quadratic. Let u = w² and rewrite as: u² + 7u - 18 = 0 (u+9)(u-2) = 0 u = -9 and 2 = w² w = ±3i and ±√2

If you have your own answer to the question How to solve the equation | m - 9 | = 27 ?, then you can write your own version, using the form below for an extended answer.